Pengembangan Digitalisasi Ekonomi Syariah di Negara Asia Tenggara - Fia Ayuning Pertiwi (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The digital economy is a new engine of sustainable development, high quality economic growth and fintech are key player in global financial markets. The goal of this study is to analyze a technological angle to better understand how digitalization has influenced the growth of the Islamic economy. Focus on literature and descriptive analysis methods, this study takes a qualitative approach to examine Islamic fintech peer to peer lending in Asia. According to the study’s findings, SME (Small Medium Enterprose) are becoming more likely to use these services as the Islamic economy becomes more digitalizes and reliant on Islamic fintech funding.